Tax Losses due to Shadow Economy Activities in OECD Countries from 2011 to 2013: A Preliminary Calculation - Friedrich Schneider (Center for Economic Studies and ifo Institute (CESifo), 2015)
In this short paper an attempt is undertaken to calculate the tax losses which result from shadow economy activities in a country. These calculations are done for the 28 EU countries, for 3 non-EU countries and for 2 other highly-developed OECD countries. The total tax losses over all 28 EU-countries make up 450.8 billion euros or 3.6% of EU-28-GDP in 2011. In 2012 it were 457.3 billion euros or 3.5% of EU-28-GDP and in 2013 454.2 billion euros or 3.4% of EU-28-GDP. For the whole country sample used in this paper the tax losses amounted to 698.7 billion euros or 2.4% of GDP of these 33 countries in 2011. In 2012 the value of tax losses was 737.2 billion euros or 2.3% of GDP and in 2013 it was 713.1 billion euros or also 2.3% of total GDP of these 33 countries.
Keywords: E26; H26; K42; O17; 330; tax losses; shadow economy; tax and social security contribution burden